Decreased immunoglobulin G levels after living‐donor liver transplantation is a risk factor for bacterial infection and sepsis. Issue 2 (5th March 2014) - Yoshizumi, T.; Shirabe, K.; Ikegami, T.; Yamashita, N.; Mano, Y.; Yoshiya, S.; Matono, R.; Harimoto, N.; Uchiyama, H.; Toshima, T.; Maehara, Y.
Abstract Background Several studies have suggested an association between post‐transplant immunoglobulin (Ig) levels and the development of infection in solid organ transplantation. We therefore conducted exploratory analyses of potential factors associated with bacterial infection/sepsis after living‐donor liver transplantation (LDLT). Methods Blood samples from 177 recipients who received primary LDLT between September 1999 and November 2011 were available for study. Hypogammaglobulinemia was defined as having at least 1 IgG level <650 mg/dL within 7 days after LDLT. Risk factors for developing post‐transplant bacterial infection and sepsis within 3 months after LDLT were analyzed. Results Fifty (28.2%) recipients experienced bacterial infection within 3 months of LDLT. Eighty‐four (47.5%) recipients had hypogammaglobulinemia, although no recipients had hypogammaglobulinemia before LDLT. Hypogammaglobulinemia, undergoing hepaticojejunostomy, and portal pressure at closure >15 mmHg were independent risk factors for developing bacterial infection within 3 months of LDLT (P < 0.0001 P = 0.0008, and P = 0.011, respectively). The odds ratio (OR) and confidence interval (CI) for hypogammaglobulinemia were 4.79 and 2.27–10.7, respectively. Twenty‐four (13.6%) recipients developed bacterial sepsis within 3 months. Hypogammaglobulinemia, operative time >14 h, model for end‐stage liver disease score >15, and no mycophenolate mofetil use were independent risk factors for developing bacterial sepsis (P = 0.009, P = 0.001, P = 0.003, and P = 0.005, respectively). The OR and CI for hypogammaglobulinemia were 3.83 and 1.38–12.0, respectively. Conclusions Hypogammaglobulinemia within 7 days of LDLT was a significant risk factor for post‐transplant bacterial infection and sepsis.